Representasi Makna Patriotisme dalam Film Genre Perang - Tzarini Ayuning Bidhuri; Aning Sofyan (Bandung Conference Series: Communication Management, 2022)
Abstract. In modern times like now, there are lots of entertainment facilities for everyone to enjoy, one of which is film. Films have various types of genres, one of which is war, which of course has the theme of patriotism. Along with the currents of modernization and globalization, of course, the sense of patriotism is not the same as before, there are gaps everywhere. Therefore, it is necessary to have a means that can convey the message of patriotism so that people can understand the meaning of patriotism, one of which is the mass media, namely film. The purpose of this research is to find out the meaning of connotations, denotations and myths contained in the scene of the film "1917", especially those which contain elements of Representation of Patriotism. In this study, researchers used qualitative methods and the Semiotic Analysis approach proposed by Roland Barthes. The data collection technique used by the researcher is Documentation and Literature Study. The result of this research is that there are elements that represent patriotism and also the meaning of denotation, connotation and myth. The meaning of denotation in this film is positive attitudes between human beings. The connotation of this film is that the attitude shown is an attitude that represents the soul of patriotism in a person. And the myth in this film is that the medal is a special award and becomes a pride for its owner, someone in a state of urgency will be selfish and don't help others, group differences become an excuse not to help each other, an optimist never feels down and people who is dying will know that he will lose his life. Abstrak. Pada zaman modern seperti sekarang banyak sekali sarana hiburan untuk semua orang nikmati, salah satunya adalah Film. Film mempunyai berbagai jenis genre salah satunya perang yang tentunya bertemakan patriotisme. Seiring dengan adanya arus modernisasi dan globalisasi, tentunya rasa patriotisme tidak sama seperti dahulu, terjadi kesenjangan di mana-mana. Maka dari itu, perlu adanya sebuah sarana yang bisa menyampaikan pesan patriotisme sehingga masyarakat dapat memahami makna patriotisme, salah satunya media massa yaitu film. Tujuan dilakukannya penelitian ini adalah untuk mengetahui makna konotasi, denotasi dan mitos yang terdapat pada adegan film “1917” khususnya yang mengandung unsur Representasi Patriotisme. Pada penelitian ini, peneliti menggunakan metode kualitatif dan pendekatan Analisis Semiotika yang dikemukakan oleh Roland Barthes. Teknik pengumpulan data yang peneliti pakai adalah Dokumentasi dan Studi Kepustakaan. Hasil penelitian ini adalah terdapatnya unsur-unsur yang merepresentasikan patriotisme dan juga makna denotasi, konotasi dan mitos. Makna denotasi pada film ini adalah sikap-sikap positif antar sesama manusia. Konotasi dari film ini adalah sikap yang ditunjukkan merupakan sikap yang merepresentasikan jiwa patriotisme dalam diri seseorang. Dan mitos pada film ini adalah medali merupakan sebuah penghargaan yang spesial dan menjadi sebuah kebanggan bagi pemiliknya, seseorang dalam keadaan mendesak akan bersifat egois dan tidak menolong orang lain, perbedaan kelompok menjadi alasan untuk tidak saling menolong, seorang yang optimis tidak pernah merasakan keterpurukan dan orang yang sedang sekarat akan mengetahui bahwa ia akan kehilangan nyawanya.